Pengaruh Pendapatan dan Altruisme terhadap Pembayaran Zakat dengan Moderasi Religiusitas di Lembaga Amil Zakat - Fatimah, Siti; Alfiyana, Eva; Endraswati, Hikmah; Fatmah, Nurul; Wibowo, Wahyu (Assyarikah: Journal of Islamic Economic Business, 2025)
Zakat is an Islamic financial instrument that plays a crucial role in wealth distribution and poverty alleviation. However, in Indonesia, the level of participation by muzakki through official zakat institutions remains relatively low. This study examines the influence of income and altruism on zakat payment decisions, considering religiosity as a moderating variable. A quantitative approach was employed, with data collected through a survey of 51 purposively selected respondents and analyzed using multiple linear regression and moderated regression analysis (MRA). The results indicate that income significantly affects zakat payment decisions, while altruism does not have a significant impact; religiosity strengthens the effect of income but does not moderate the relationship between altruism and zakat decisions. These findings highlight the importance of the spiritual dimension in encouraging zakat compliance and provide a basis for zakat institutions to develop educational and spiritual strategies aimed at enhancing zakat collection more effectively.